Spanish Syllables Recognition by Wavelet and Cross Covariance - Soto-Gomez, J; San Juan-Urrutia, E; Canete-Arratia, L; Canete-Arratia, L; Adasme-Soto, P (Institute of Electrical and Electronics Engineers Inc., 2019)
This paper shows the recognition of syllables through the using of Wavelet Transform and statistical tools such as cross covariance and the Pearson correlation coefficient. The considered syllables in this work are Consonant-Vowel (CV) and Vowel-Consonant (VC) given that they constitute 60% of those present in the Spanish language. The signals of the syllables are processed through a focused analysis with the application of time windows (segmentation the syllables in their respective phonemes) to later perform a multi-resolution analysis using the Wavelet Transform. For the recognition of the CV or VC structure, the cross covariance and the Pearson correlation coefficient are used. The results shows the performance of proposed method in comparison with other methods. © 2019 IEEE.